Regret about the timing of first sexual intercourse: The role of age and context - Richard Layte; Hannah McGee (The Economic and Social Research Institute (ESRI), 2007)
Objective: To examine how age at first vaginal intercourse is related to the circumstances of sex and specifically to the nature of the relationship between the partners, levels of autonomy, planning and regret. To quantify the contribution of age at first sex relative to the context and circumstances of sex. Design: Cross-sectional survey of sexual knowledge, attitudes and behaviours of the Irish population carried out by telephone in 2005/6. Participants: A nationally representative sample of the population of the Republic of Ireland aged 18 to 64 years (n=7441:3188 men and 4253 women). Results: The median age of first vaginal sex was 18 for men and 19 for women. Median age at first sex had decreased by 4 years for men and 5 years for women over the last five decades. Sex was a 'spur of the moment' decision for 39% of men and 29% of women who had vaginal sex for the first time when they were aged 20+ compared to 74% of men and 56% of women who had sex at age 15 or less. Less than 1% of men and women whose first experience of intercourse occurred over the age of 20+ were unwilling or forced. These figures were 8% of men and 27% of women among those whose first sex was at age 15 or younger. A substantial minority (14% of men and 19% of women) said they wished that they had waited longer before having their first sexual experience. This increased to 28% of men and 52% of women who had their first sex before the age of 17. Controlling for age of first sex, the context and circumstances remain important predictors of subsequent regret. Conclusions: Younger age at first sex was associated with weaker planning, lower autonomy, a less stable relationship with partner and higher levels of regret. However, regret after early sexual initiation was not universal and young age per se was not responsible for higher levels of regret. Instead, the lower knowledge and skills of early debutants and their impact on levels of planning, preparedness and willingness lead to later regret.
Keywords: 330; First sexual intercourse; willingness; planning; regret; Sexualität; Irland